Aquatic organic matter fluorescence - Coble, Paula G. (Cambridge : Cambridge University Press, 2014)
This is the first comprehensive text on the theory and practice of aquatic organic matter fluorescence analysis, written by the experts who pioneered the research area. This book covers the topic in the broadest possible terms, providing a common reference for making measurements that are comparable across disciplines, and allowing consistent interpretation of data and results. The book includes the fundamental physics and chemistry of organic matter fluorescence, as well as the effects of environmental factors. All aspects of sample handling, data processing, and the operation of both field and laboratory instrumentation are included, providing the practical advice required for successful fluorescence analyses. Advanced methods for data interpretation and modeling, including parallel factor analysis, are also discussed. The book will interest those establishing field, laboratory, or industrial applications of fluorescence, including advanced students and researchers in environmental chemistry, marine science, environmental geosciences, environmental engineering, soil science, and physical geography.
Part I. Introduction. 1. The principals of fluorescence / Darren M. Reynolds ; 2. Fluorescence and dissolved organic matter : a chemist's perspective / George Aiken ; 3. Aquatic organic matter fluorescence / Paula G. Coble, Robert G.M. Spencer, Andy Baker, and Darren M. Reynolds -- Part II. Instrumentation and Sampling. 4. Sampling design for organic matter fluorescence analysis / Robert G.M. Spencer and Paula G. Coble ; 5. Optical spectroscopy instrumentation design, quality assurance and control : bench-top fluorimetry / John R. Gilchrist and Darren M. Reynolds ; 6. Experimental design and quality assurance : in-situ instrumentation / Robyn N. Conmy, Carlos E. Del Castillo, Bryan D. Downing, and Robert F. Chen -- Part III. Environmental Effects. 7. Physicochemical effects on dissolved organic matter fluorescence in natural waters / Christopher L. Osburn, Rossana Del Vecchio, and Thomas J. Boyd ; 8. Biological origins and fate of fluorescent dissolved organic matter in aquatic environments / Colin A. Stedmon and Rose M. Cory -- Part IV. Interpretation and Classification. 9. Fluorescence indices and their interpretation / Rachel S. Gabor, Andy Baker, Diane M. McKnight, and Matthew P. Miller ; 10. Chemometric analysis of organic matter fluorescence / Kathleen R. Murphy, Rasmus Bro, and Colin A. Stedmon.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Chemical oceanography; Water chemistry; Biogeochemistry; Seawater -- Organic compound content; Bioluminescence